Management of action research in school: a bibliometric analysis - Moktar, Azlin; Alias, Bity Salwana; Rasul, Mohamad Sattar (Institute of Advanced Engineering and Science, 2025)
This paper employs bibliometric analysis and visualization techniques, including VOS Viewer, to scrutinize trends in managing action research in schools. Utilizing a dataset of 337 articles sourced from Web of Science (WoS) until 2023, the study adheres to PRISMA guidelines to systematically examine authorship patterns, trends, and themes. The analysis reveals a surge in publication rates and a focus on collaborative problem-solving, inclusivity, and global perspectives, with notable contributions from journals like educational action research and authors (such as Wood). Diverse author collaborations and global representation underscore interconnected research themes. Additionally, four distinct clusters—knowledge and leadership, action research and engagement, caring and impact, and empowerment and participation—emerge, encapsulating action research management in schools. However, challenges such as limited discussion platforms, resource constraints, and contextual barriers persist, necessitating enhanced reflective practices and collaborative learning. While bibliometric analysis provides quantitative insights, the study advocates for complementing such approaches with qualitative methods to ensure a comprehensive understanding of action research management in schools, guiding future strategies in educational research.